Hotspot-Limited Microprocessors Direct Temperature and Power Distribution Measurements. - Hamann, H. F.
An experimental technique is presented, which allows for spatially-resolved imaging of microprocessor power (SIMP). In a first step this method utilizes infrared (IR) thermal imaging, while the processor is effectively cooled using an IR-transparent heat sink. In the second step the underlying power distribution is derived by determining the temperature fields for each individual power source on the chip. The measured chip temperature distribution is represented as a superposition of these temperature fields. The SIMP data reveals significant temporal and spatial variations of the microprocessor power/temperature distribution, which can be attributed to the circuit layout as well as to the varying utilization levels across the processor while running full workloads. In this paper we have applied the SIMP method to the dual core PowerPCtrade970MP microprocessor to measure detailed temperature and power distributions under full operating conditions. In the first part of the paper the impact of power and temperature limitations of high performance CMOS chips is discussed in detail, where we distinguish between hotspot-limited (or temperature-limited) and power-limited chips. The discussion shows the importance of temperature and power distributions for chip floor planning, layout, design and architecture. Second, we present the experimental details of the SIMP method, which is applied to the dual core PowerPC970MP to directly measure the temperature and power fields as a function of workload and frequency. A pronounced movement of the hotspot location is observed. Finally, the hotspot of a competitive microprocessor is compared by measuring temperature efficiencies (temperature increase/performance) for the same workloads and cooling conditions
Keywords: CMOS chips; IR transparent heat sink; PowerPC 970MP microprocessor; SIMP method; Circuit layout; Cooling; Hotspot location; Hotspot-limited chips; Hotspot-limited microprocessors; Infrared thermal imaging; Microprocessor power distribution; Microprocessor temperature distribution; Microprocessor testing; Power distribution measurement; Power-limited chips; Spatially-resolved imaging; Temperature fields; Temperature measurement; Temperature-limited chips